Emotional disorders in response to the impact of Covid-19 in psychology students from Lima and Ica (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2021)
The objective of the research was to determine the levels of maladaptive responses and, consequently, emotional disorders in response to the impact of Covid-19, based on José Anicama’s cognitive-behavioral approach. The study is non-experimental, descriptive-comparative, and the population consisted of 100 psychology students from Lima and Ica. Data collection was carried out using Anicama’s API Scale. The findings revealed high and average levels of maladaptive emotional behavior caused by Covid-19, with symptoms of anxiety, depression, phobias, and stress.